2020
DOI: 10.3389/fonc.2020.01487
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Epstein-Barr Virus-Deoxyribonucleic Acid Copy Number Predicts Disease Progression in Stage I–III Pulmonary Lymphoepithelioma-Like Carcinoma

Abstract: Purpose: To investigate the predictive values of plasma Epstein-Barr Virus (EBV)-deoxyribonucleic acid (DNA) copy number on disease progression and survival in stage I-III pulmonary lymphoepithelioma-like carcinoma (LELC). Patients and Methods: Patients with pathologically confirmed, initially diagnosed or locally recurrent stage I-III pulmonary LELC, who received locally radical treatment and had plasma EBV-DNA results, were retrospectively reviewed. Risk factors of progression-free survival (PFS) and overall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(12 citation statements)
references
References 24 publications
(34 reference statements)
0
12
0
Order By: Relevance
“…A related report of EBV‐DNA in LEC outside the nasopharynx is additionally documented in the literature. Li and co‐workers confirmed that increased plasma EBV‐DNA >1000 copies/ml is strongly predictive of pulmonary LEC progression within 3 months, with a specificity of 97.5% (95% CI: 86.8%–99.6%), and associated with impaired OS (2‐year OS, >1000 and ≤ 1000 copies/ml, 72.9% and 100%, p < 0.001) 34 . In the present study, we further investigated the prognostic value of plasma EBV‐DNA load in NNPLEC.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…A related report of EBV‐DNA in LEC outside the nasopharynx is additionally documented in the literature. Li and co‐workers confirmed that increased plasma EBV‐DNA >1000 copies/ml is strongly predictive of pulmonary LEC progression within 3 months, with a specificity of 97.5% (95% CI: 86.8%–99.6%), and associated with impaired OS (2‐year OS, >1000 and ≤ 1000 copies/ml, 72.9% and 100%, p < 0.001) 34 . In the present study, we further investigated the prognostic value of plasma EBV‐DNA load in NNPLEC.…”
Section: Discussionmentioning
confidence: 95%
“…Li and co-workers confirmed that increased plasma EBV-DNA >1000 copies/ml is strongly predictive of pulmonary LEC progression within 3 months, with a specificity of 97.5% (95% CI: 86.8%-99.6%), and associated with impaired OS (2-year OS, >1000 and ≤ 1000 copies/ml, 72.9% and 100%, p < 0.001). 34 In the present study, we further investigated the prognostic value of plasma EBV-DNA load in NNPLEC. Notably, OS and PFS were significantly lower among patients with pretreatment plasma EBV-DNA loads of ≥2280 copies/ml relative to those with loads of <2280 copies/ml.…”
Section: Discussionmentioning
confidence: 97%
“…These seven studies (two prospective and five retrospective studies, published between 2004 and 2021) involved 795 patients 13,14,20,24–27 . The sample types used in these studies were plasma in four studies and serum in the other three studies.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, the cut‐off value of EBV DNA used in this study was 236 copies/ml, which was much lower than that in other studies, and different cut‐off values had varied effects on the results. Furthermore, Li et al 20 demonstrated that pretreatment EBV DNA > 10 000 copies/ml or positive posttreatment EBV DNA predicted poor PFS but had no significant correlation with OS. This phenomenon could be attributed to the fact that only patients diagnosed with localized disease and who received radical treatments were included in the study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation